The Importance of Corporate Governance of Banks Concerning the Ownership in the International Environment - Mejra Festić; Polona Črepinko; Borut Bratina (Naše gospodarstvo/Our economy, 2022)
The analysis of the factors of corporate governance is divided into four thematic sections. In the first part corporate governance is defined as part of the broader economic context. The second part deals with the princi- ples of corporate governance. In the third part, the relation between the index of corporate governance and individual indicators (an indicator of commitment, transparency, and disclosure, caring for partners, and control and audit) regarding ownership is defined. An analysis was undertaken for the countries of Central and Eastern Europe. A higher level of foreign own- ership had a positive correlation with the corporate governance index. On the other hand, the correlation between state ownership and corporate gov- ernance index was not clear. The prevention of poor banking practices does not only lie in controlling functions, but also in the general corporate and risk-taking cultures, and the social perception of managerial roles, regard- less of ownership structure.